Efektivitas Pemanfaatan Lingkungan Sekolah Sebagai Sumber Belajar Terhadap Hasil Belajar IPA Tema 6 Subtema 1 Kelas IV SD Negeri 122349 Pematang Siantar T.A 2022/2023 - Noviawanda, Nasya; Ananda, Lala Jelita; Lubis, Wildansyah; Rangkuti, Irsan; Rozi, Fahrur (Universitas Labuhanbatu, 2023)
The background to research at SDN 122349 Pematang Siantar found several problems, namely 1) The teacher only relied on textbooks as a learning resource, 2) Students quickly felt bored in teaching and learning activities using the lecture method, so this became one of the learning factors become less effective and learning outcomes are less than optimal, 3) Science learning outcomes of students in class IV A are still in the low category, 4) Teachers still do not maximize the quality of learning by using various learning resources in the teaching and learning process. The purpose of this study was to find out 1) The effectiveness of using the school environment as a learning resource on learning outcomes in Science Theme 6 Sub-theme 1 Learning 1 in Class IV A SDN 122349 Pematang Siantar T.A 2022/2023. 2) Student science learning outcomes in Theme 6 Sub-theme 1 Learning 1 in class IV A SDN 122349 Pematang Siantar T.A 2022/2023. This type of research is correlational research. The subjects in this study were 28 students in class IV A. The research instrument used was multiple choice tests and learning observation sheets. The percentage results show that 1) The results obtained increased from the pre-test value of 14% to 100%. It can be concluded that by utilizing the school environment as a learning resource it can improve learning outcomes Science Theme 6 Sub-theme 1 Learning 1 Class IV SDN 122349 Pematang Siantar T.A 2022/2023. 2) From the calculation of the t test obtained tcount = 4.65 and ttable = 2.056. So it can be concluded that tcount > ttable, then H1 is accepted and H0 is rejected.